2014
DOI: 10.1007/s00330-014-3407-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medial patellofemoral ligament tears after acute lateral patellar dislocation: comparison of high-frequency ultrasound and MR

Abstract: • High-frequency ultrasound and MR were able to detect MPFL lesions after acute lateral patellar dislocation. • High-frequency ultrasound and MR showed similarly high accuracy in diagnosing MPFL lesions. • Interobserver agreement was very good for high-frequency ultrasound and good for MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Firstly, the injury patterns of the MPFL and articular cartilage lesions were not evaluated surgically but based on the MRIs only; therefore, we were unable to determine the accuracy of these MRI findings. Nonetheless, previous studies have shown that MRI is an accurate method for the diagnosis of the MPFL injury after acute LPD [4,5,8,11,17,22]. Our study results also showed that the interobserver agreement was good for the evaluation of injury types of the MPFL and very good for the evaluation of injury locations of the MPFL.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Firstly, the injury patterns of the MPFL and articular cartilage lesions were not evaluated surgically but based on the MRIs only; therefore, we were unable to determine the accuracy of these MRI findings. Nonetheless, previous studies have shown that MRI is an accurate method for the diagnosis of the MPFL injury after acute LPD [4,5,8,11,17,22]. Our study results also showed that the interobserver agreement was good for the evaluation of injury types of the MPFL and very good for the evaluation of injury locations of the MPFL.…”
Section: Discussionsupporting
confidence: 69%
“…Injuries occurred simultaneously in more than one location of the MPFL were classified as combined injury [3,4,8,22]. Articular cartilage lesion was divided into chondral lesions and osteochondral lesions [23].…”
Section: Mri Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were eligible for inclusion if they had suffered an acute, first-time LPD regardless of the injury mechanism. The inclusion criteria were as follows ( 17 18 19 20 21 ):…”
Section: Methodsmentioning
confidence: 99%
“…Using the diagnostic classification criteria from studies of Zhang et al and Balcarek et al ( 17 18 19 20 21 22 23 24 ), the degrees of MPFL injury were divided into partial and complete tears. The manifestations of a partial MPFL tear were defined as thickening and irregularity of the contour, including discontinuity of normal fibers, and intraligamentous or extensive periligamentous edema.…”
Section: Methodsmentioning
confidence: 99%